The Functional Requirements for Bibliographic Records (FRBR), its Relationship with the GDR and the Changes that lie ahead - Calvo Sánchez, Loirette (2017)
The field of the information organization is going through an accelerated transformation due to the explotion of the information, to the diversity of support and to the development of the web environments, what has given place to a series of change in the treatment of information. Consequently this investigation pretends to identify what constitutes the model of related identity proposed by the IFLA denominated FRBR (Functional Requirements for Bibliographic Records). What are the Principles of Paris, Cataloging International Principles and in what way influences them in the drafting of the RDA and which are the changes reflected in the RDA (Resources Description & Access) in relation with the AACR2.